Evaluate of Lindi Processing Technology in TPA Pojok Kota Kediri - Lois Aprilia Irianti; Ratna Wardani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
One of the problems in the final processing site (TPA) is the presence of leachate. Leachate often collects at the midpoint of the landfill. Leachate contains various chemical derivatives from the dissolving of waste in the landfill and the results of chemical and biochemical reactions that occur in the landfill. The purpose of this study was to determine the technology used in the TPA Pojok Kota Kediri in processing existing leachate. This type of research is qualitative research. This study uses a qualitative approach because the researcher wants to explore, review, and describe a technology directly. In this study, the researchers wanted to explore directly and review how the existing technology in the Pojok TPA in processing the existing leachate. There are seven informants in this study consisting of six special workers who handle leachate and triangulation. Other tools used are friends, cellphones, then documented in the form of a transcript. Data processing was carried out by means of content descriptive. Subsequently reported and presented in a descriptive description. The results of the study indicate that the technology used by the TPA Pojok Kota Kediri in processing its leachate is the Wetland method. To determine the level of success of this technology is to use aquatic plants such as water spinach and water hyacinth which have been proven to survive so far. The technology used by TPA Pojok Kota Kediri is in accordance with existing government regulations, but it must continue to make improvements to the wetland pond which is still not maximally used.